Analyzing the Impact of Islamic Literacy, Technology, and Experience on MSME Performance: The Role of Spirituality as a Moderating Variable - Widyakto, Adhi; Souisa, Johanis; Kusumawati, Citra Andriani; Widyarti, Endang Tri (Universitas Muhammadiyah Yogyakarta, 2024)
Research Aims: This study aims to explore the influence of Islamic financial literacy, Islamic fintech, and financial experience on the performance of Micro, Small, and Medium Enterprises (MSMEs), considering spirituality as a potential moderating variable.Design/Methodology/Approach: Employing a sample of 126 MSME owners in Semarang, this research utilizes Hair’s model of calculations. The analytical method applied is multiple regression analysis using the third version of the SmartPLS software.Research Findings: The findings indicate that Islamic financial literacy, Islamic financial technology, and financial experience have a positive and significant impact on MSME performance. However, spirituality did not significantly moderate the relationship between Islamic financial literacy, Islamic fintech, and financial experience on MSME performance.Theoretical Contribution/Originality: This study contributes to the resource-based view theory by examining how a firm’s capabilities and internal resources, conceptualized as a bundle of resources and capabilities, interact with external spiritual values to influence MSME performance. It also addresses the role of internal resources in fostering competition within firms to achieve their goals.